Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/jcm.02659-12
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Stability of Pathogen-Specific Nucleic Acid Targets in Clinical Samples

Abstract: bThe stability of pathogen-specific DNA or RNA amplification targets in clinical samples following short-term storage at room temperature, 4°C, and ؊80°C was assessed by real-time PCR. In purified nucleic acid extracts, both DNA and RNA targets were stable for up to 30 days, irrespective of storage temperature. In unextracted samples, temperature-dependent loss of targets (P < 0.05) was observed in serum and cerebrospinal fluid specimens, while no changes were observed for EDTA blood samples. N ucleic acid amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…However, studies on other pathogens in different clinical specimens have shown a negative effect on molecular testing when kept at ambient temperature for extended periods of time (Hasan et al, 2012, Ingersoll et al, 2008. In that context, the manufacturer of the Xpert assay recommends that sputum samples be kept for no longer than 3 days at ambient temperatures up to 35° C until processing (Banada, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on other pathogens in different clinical specimens have shown a negative effect on molecular testing when kept at ambient temperature for extended periods of time (Hasan et al, 2012, Ingersoll et al, 2008. In that context, the manufacturer of the Xpert assay recommends that sputum samples be kept for no longer than 3 days at ambient temperatures up to 35° C until processing (Banada, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, they found that CMV in serum stored at room temperature had a half-life of less than one day when quantified by PCR. 16 A study investigating the stability of viral DNA in CSF samples found no decline in HSV quantity using PCR after one month regardless of storage temperature. 7 However, another study found that storing dried blood spots at 37 °C for 1 year significantly diminished the yield of HIV-1 DNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in this study we compared EDTA-anticoagulated blood collected by venipuncture and capillary blood samples that were deposited onto viscose swab devices, exhibiting no anticoagulation activity. Protective effects of EDTA on stability of pathogen-derived RNA in blood samples have been reported [ 26 ]. Despite this fact, we haven chosen these swab devices for our comparison study, as the European Mobile Laboratory units in Guéckédou, Guinea, and Foya, Liberia, received a considerable number of capillary blood samples absorbed onto viscose swabs as a diagnostic sample specimen from both infants and adults for EVD testing (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%